Memahami Kaidah Ushuliyah Al-Am, Al-Khas, Al-Amru dan An-Nahyu Sebagai Metodologi Penetapan Hukum Islam - Muh Alghifari; Nurul Safitri; Linda Oktaviana; Kurniati Kurniati (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
There are at least three problems that will arise if the establishment of the Islamic law ignores the Ushuli theory; the ambiguity in the use of Ushuli theory, the misunderstanding of the Nash in the Qur'an and Hadith, and the broad interpretation because it does not focus on one or more of the Uushuri theories. The purpose of the study is to know the approach of the Ushuliyah al-am, al-khas, al-amru and al-nahyu as methodologies, procedures, and problems in the establishment of Islamic law. This research is a qualitative library research with a Ushul Fiqh approach. It is the same in the Qur'an as in the Quran. The procedure for the establishment of Islamic law is not much different from some of the views of scholars conducted, in general, namely by searching for the provisions of the law in Al-Qu’an and Hadith and analogous to the Islamic Shariah. The problem is that it lies at the core of the beginning of the law, on the different understanding and meaning that is presented or expressed by the scholars, the solution to overcome this problem by following the agreement of the scholar. Thus, in the understanding of the teachings of the Ushuri: Al-Am, Al-Khas, al-Amru and An-Nahyu, which is a small part of the studies of Ushuli, open a great opportunity for further research to discuss more fully about the teaching of Ussuri than Al-Amm, Al - Khas, Amru and Al – Nahyu.